2017
DOI: 10.1186/s40249-017-0296-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-locus variable-number tandem repeat analysis of Chinese Brucella strains isolated from 1953 to 2013

Abstract: BackgroundBrucellosis was a common human and livestock disease caused by Brucella strains, the category B priority pathogens by the US Center for Disease Control (CDC). Identified as a priority disease in human and livestock populations, the increasing incidence in recent years in China needs urgent control measures for this disease but the molecular background important for monitoring the epidemiology of Brucella strains at the national level is still lacking.MethodsA total of 600 Brucella isolates collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 18 publications
3
34
0
Order By: Relevance
“…The results also showed that B. melitensis was a predominant species in sheep and that most B. melitensis strains (71%) were subgrouped into the East Mediterranean group (genotype 42). These strains may be epidemiologically linked, some evidence of which was provided by the MLVA‐11 of these isolates in conjunction with 600 other strains from different regions in China (Tian et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results also showed that B. melitensis was a predominant species in sheep and that most B. melitensis strains (71%) were subgrouped into the East Mediterranean group (genotype 42). These strains may be epidemiologically linked, some evidence of which was provided by the MLVA‐11 of these isolates in conjunction with 600 other strains from different regions in China (Tian et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Multilocus variable‐number tandem‐repeat analysis‐11 of 66 isolates found a novel genotype (genotype 369: 1‐5‐3‐13‐2‐2‐3‐2‐7‐41‐8), which emerged in panel 2B when the isolates were compared with other strains from different regions in China (Liu et al., ; Tian et al., ). The analysis indicated a dominant Brucella genotype that was relatively stable, but variations emerged in panel 2B within the bruce04, bruce16 and bruce30 loci.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations